Designing methods for the monitoring and evaluation of household food security in IFAD-funded rural development projects: Technical Guide: Strengthening the Household Food Security and Nutritional Aspects of IFAD Poverty Alleviation Projects: Developing Operational Methodologies for Project Design and Monitoring - Carletto, Calogero; Morris, Saul Sutkover (International Food Policy Research Institute, 1999)
In recent years, many development agencies have made intensive efforts to improve their efficiency and increase their impact on rural poverty. At the heart of this new strategic management process is the measurement of performance. With Household Food Security (HFS) and nutritional security now clearly identified as desired outcomes of many development projects, there is a need to assess the performance of investment projects in terms of their impact on the HFS and nutrition status of their targets groups.This guide emphasizes the design of quantitative impact evaluation exercises for HFS and nutrition, and provides development practitioners with the basic principles on why, when and how to choose and implement a particular evaluation system. We argue that two of the key features of a good impact evaluation study are the availability of accurate baseline information and a properly thought-out control group, respectively allowing for before-after and with-without comparisons. The importance of a joint temporal and cross-sectional comparison of the beneficiary group against a counterfactual is crucial to simultaneously control for the effects of all sorts of external factors likely to contaminate the impact evaluation results. We also argue that the involvement of the evaluation team in the earliest stages of project design stage is the most suitable way to ensure a proper and accurate evaluation without having to rely on more complicated statistical techniques, as well as to permit a sound learning process to ensue from the evaluation exercise. However, if the conditions dictate, statistical techniques can still provide the evaluation team with effective tools for a well-founded impact evaluation. In the following sections we draw on seminal work recently completed by the UNICEF Evaluation Office, in an attempt to provide the reader with the conceptual underpinnings for the choice of a particular design suited to the type and the level of accuracy of the information required by the different intended end-users. In the second part of the document, we report on two of the evaluation methodologies used in the field in the course of projects focused on strengthening HFS and nutritional aspects of poverty alleviation projects.